Optimization of the Sybr Green real time PCR for the detection of Human Herpes Virus type 6 (HHV-6) Otimização da PCR em tempo real - Sybr Green para detecção do Herpes Vírus Humano tipo 6 (HHV-6) - Cynthia Liliane Motta do Canto; Laura Massami Sumita; Adriana Freire Machado; Adriana Tateno; Eveline Vieira da Cunha; Clarisse Martins Machado (Revista do Instituto de Medicina Tropical de São Paulo, 2008)
HHV-6 is the etiological agent of Exanthem subitum which is considered the sixth most frequent disease in infancy. In immuno-compromised hosts, reactivation of latent HHV-6 infection may cause severe acute disease. We developed a Sybr Green Real Time PCR for HHV-6 and compared the results with nested conventional PCR. A 214 pb PCR derived fragment was cloned using pGEM-T easy from Promega system. Subsequently, serial dilutions were made in a pool of negative leucocytes from 10-6 ng/µL (equivalent to 2465.8 molecules/µL) to 10-9 (equivalent to 2.46 molecules/µL). Dilutions of the plasmid were amplified by Sybr Green Real Time PCR, using primers HHV3 (5' TTG TGC GGG TCC GTT CCC ATC ATA 3)'and HHV4 (5' TCG GGA TAG AAA AAC CTA ATC CCT 3') and by conventional nested PCR using primers HHV1 (outer): 5'CAA TGC TTT TCT AGC CGC CTC TTC 3'; HHV2 (outer): 5' ACA TCT ATA ATT TTA GAC GAT CCC 3'; HHV3 (inner) and HHV4 (inner) 3'. The detection threshold was determined by plasmid serial dilutions. Threshold for Sybr Green real time PCR was 24.6 molecules/µL and for the nested PCR was 2.46 molecules/µL. We chose the Real Time PCR for diagnosing and quantifying HHV-6 DNA from samples using the new Sybr Green chemistry due to its sensitivity and lower risk of contamination. HHV-6 é o agente etiológico do Exantema Súbito e considerado a sexta doença mais comum na infância. Em indivíduos imunocomprometidos, a reativação da infecção latente pode causar doença aguda ou morte. Padronizamos PCR em Tempo Real utilizando a química Sybr Green na detecção do HHV-6 e comparamos os resultados com a PCR convencional. Um fragmento de 214 pb foi clonado através do kit pGEM-T do sistema Promega. Com este clone, foram feitas diluições seriadas em um pool de leucócitos negativos a partir de 10-6 ng/µL (equivalente a 2465,8 moleculas/µL) até 10-9 (equivalente a 2,46 moleculas/µL). As diluições foram amplificadas por PCR em Tempo Real utilizando Sybr Green, com primers HHV3 5' TTG TGC GGG TCC GTT CCC ATC ATA 3' e HHV4 5' TCG GGA TAG AAA AAC CTA ATC ...